PEMBENTUKAN KARAKTER BERBASIS PENDIDIKAN PESANTREN: Studi di Pondok Pesantren Tradisional dan Modern di Kabupaten Ponorogo - H.A. Rodli Makmun (Cendekia: Kependidikan dan Kemasyarakatan, 2014)
Abstract: Character education meant as value education, ethic kindness education,moral education, which its aim to developingparticipant ability in order to give decisionof good-bad, looking after of goodness, and realize that kindliness in everyday life obligingly. In consequence character education as psychologically include dimension;moral reasoning, moral feeling, and moral of behavior.Character education inIslamic Boarding School conducted integrally with educationprocess in Islamic Boarding School. Character education do not become separate teaching item. It is true there isspecial subject of behavior, namely baninlilakhla, al-nawbawiakhlaq, makhfudhat, interpretation, hadits, and so on, but that study havegeneral nature to add knowledge of santri, forming patterned thinking and santri behavior. Santricharacter formed by the sake of Allah, serving, respecting, down to earth, modestly, self-serving, and free in Islamic Boarding School community. IslamicBoarding School design inuring pattern during 24 hour in Islamic Boarding School.Santricharacter of traditional Islamic Boarding Schoolturn to yellow bookfrom studyingand habituation in order toobeyIslamic Boarding School orders  سرادلما .ةيفلسلاو ،ةثيدحو يديلقتلا طمنلاو ،ةفلتمخ للاظ ةثلاث عقاولا في اهيدل ةيلخادلا ةيملاسلإا سرادلما ةثيدلحا ىدهو ةيلخاد ةسردم ةيملاسلإا ىدلها راد لاثلما ليبس ىلع ةشوقنم ؤجؤنؤف في ةيلخادلا ةيملاسلإا ،وغنوس يلاو ةيلخادلا ةيملاسلإا سرادلماو ،ةثيدلحا ةرجلحا كودنوب كانه نأ ينح في ىنم ةشوقنم يديلقتلا.نايمإ لآ كودنوب ةيلخادلا ةيملاسلإا سرادلماو ييجرخ نم ،كلذلو .ةيصخش نيوكت ىلع يرثأت اله نوكي ةيلخادلا ةيملاسلإا سرادلما لبق نم دمتعلما ماظنلا هنلأ ،نيرخلآا ةيلخادلا ةيملاسلإا سرادلما ينيجرلخا عم ةيصخشو ةفلتمخ فقاوم اهيدل ةيلخادلا سرادلما أزجتي لا اءزج نوكتل ةيلخاد ةسردم في فرح ميلعتلا .سرد ثيح طنم ةيلخاد ةسردم نم لكشو رثأت في .اهب ةصالخا ةيميلعتلا داولما نم دحاو فرح ميلعتلا حبصي لا .ةيلخادلا سرادلما في ميلعتلا ةيلمع نم تلقنو ،يوبنلا قلاخلأاو يننبلا ليللا قلاخلأا يأ ،كولسلا اصيصخ صحفت تيلا ينعلا ميلعت كانه عقاولا كولسلا طانمأو يركفتلا طانمأ ليكشتو ،بلاطلا عيسوتل ماع ميلعت وه انمإو ،ارج ملهو ،ثيدلحا ،قيلعتلاو.بلاطلا ىدل